Clinical pharmacist interventions in medication review for medication optimization in older hospitalized adults with mental disorders and somatic comorbidities: evidence from retrospective study - Stuhec, Matej; Svetanic, Nusa; Vovk, Tomaz; Gorjan Gazdag, Anteja; Cuk, Zala; Batinic, Borjanka (Frontiers in Pharmacology, 2025)
IntroductionCollaboration with clinical pharmacists in the medication review process can potentially optimize pharmacotherapy for elderly patients with mental disorders and somatic comorbidities.AimThis study aimed to evaluate the impact of clinical pharmacists’ recommendations during medication reviews, including changes in the number of medications, potentially inappropriate medications (PIMs), potential drug-drug interactions (DDIs), and adherence to treatment guidelines.MethodsA retrospective, non-interventional study was conducted in a psychiatric hospital in Slovenia. The study included inpatients aged ≥65 years with mental disorders who were referred for medication reviews between 2013 and 2018 and had at least one therapy modification related to somatic comorbidities (heart failure, arterial hypertension, or diabetes). Clinical pharmacists conducted type 3 medication reviews (advanced medication reviews), as defined by the Pharmaceutical Care Network Europe They recorded their recommendations in the hospital’s electronic system immediately after completing the medication review. Data from before (before the medication review) and after (outcomes extracted from the electronic system at discharge) were systematically reviewed. The primary outcomes were changes in the number of medications, PIMs, and DDIs before and after the intervention. The secondary outcome was adherence to treatment guidelines for somatic comorbidities (heart failure, arterial hypertension, and diabetes).ResultsThe study included 100 inpatients with a mean age of 78.1 years (SD = 6.78). The total number of medications decreased by 6.6% (from 1,144 to 1,068; p < 0.001), with an acceptance rate of 59.2%. After the review, X-type DDIs decreased by 75.8% (from 33 to 8; p < 0.001), and D-type DDIs decreased by 56.9% (from 188 to 81; p < 0.001). The number of PIMs also significantly decreased (p < 0.001), with reductions of 29.5% (from 308 to 217) based on the Priscus List and 17.5% (from 343 to 283) according to the Beers Criteria. Adherence to treatment guidelines for somatic comorbidities improved significantly (from 3.3%–13.2% to 50.0%–72.6%; p < 0.001).ConclusionThis study demonstrates that interventions by clinical pharmacists during the medication review process effectively reduced the number of medications, PIMs, and DDIs while significantly improving adherence to treatment guidelines.